Negative plate and preparation method thereof, battery and electric equipment

By installing a flexible polymer layer outside the negative electrode current collector of the negative electrode sheet to buffer the sharp protrusion of the negative electrode active material layer and the effect between the separator, the problem of local deformation or damage of the negative electrode sheet during the hot pressing process is solved, and the flexibility of the negative electrode sheet and the cycling performance of the battery are improved.

CN119764612APending Publication Date: 2025-04-04BYD CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411566612.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the negative electrode sheet is prone to local deformation or damage during the hot pressing process, increasing the risk of short circuit. At the same time, the negative electrode sheet is poor in flexibility and easily dissipate material when bending.

Method used

A polymer layer is provided outside the negative electrode current collector, and the layer is made of flexible polymers such as polyether polyurethane, polyacrylonitrile, etc., to buffer the effect between the sharp protrusions of the negative electrode active material layer and the separator, reduce the risk of short circuit and improve flexibility.

Benefits of technology

It effectively reduces the risk of local deformation or damage of the diaphragm, improves the flexibility of the negative electrode sheet, reduces the short-circuit rate of the battery during the lamination process, and improves the cycling performance and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764612A_ABST
    Figure CN119764612A_ABST
Patent Text Reader

Abstract

The invention discloses a negative plate and a preparation method thereof, a battery and electric equipment. The negative plate comprises a negative current collector, a negative active material layer and a polymer layer. The polymer layer comprises a flexible polymer, and the flexible polymer comprises at least one of polyether polyurethane, polyacrylonitrile, polyvinyl alcohol, polyvinyl chloride and polyacrylate. According to the negative plate provided by the invention, the polymer layer is arranged on the negative active material layer outside the negative current collector, and the polymer layer plays a buffering role between the sharp bulge of the negative active material layer and the diaphragm, so that the acting force of the sharp bulge position on the diaphragm can be reduced, and the interface between the diaphragm and the negative plate in the hot pressing process is smoother; the risk of local deformation or damage of the diaphragm can be reduced; and the negative active material layer can be protected, the flexibility of the negative plate can be improved, the material falling in the bending process of the plate can be improved, and the short-circuit rate of the battery in the lamination process can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a preparation method thereof, a battery and an electrical device. Background Art

[0002] In the related art, hard carbon materials are often used as one of the negative electrode active materials in negative electrode sheets. Hard carbon particles are mostly multi-faceted irregular block morphology with sharp edges and corners. After rolling, sharp protrusions are formed on the surface of the active material layer, which makes the insulation gap of the diaphragm smaller after hot pressing, and it is easy to scratch the diaphragm during the hot pressing process, causing a short circuit. At the same time, the flexibility of the negative electrode sheet is poor, which makes it easy for the negative electrode sheet to fall off when it is bent, increasing the risk of short circuit. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first purpose of the present invention is to provide a negative electrode sheet that can reduce the risk of local deformation or damage of the separator during the lamination process (including hot pressing), and is also beneficial to protecting the negative electrode active material layer, improving the flexibility of the negative electrode sheet, and improving the material drop during the bending process of the electrode sheet, which is beneficial to reducing the short circuit rate of the battery during the lamination process.

[0004] The second object of the present invention is to provide a method for preparing a negative electrode sheet.

[0005] The third object of the present invention is to provide a battery.

[0006] A fourth object of the present invention is to provide an electrical device.

[0007] According to the first aspect of the present invention, the negative electrode sheet of the embodiment comprises: a negative electrode current collector; a negative electrode active material layer, wherein the negative electrode active material layer is arranged on the negative electrode current collector; a polymer layer, wherein the polymer layer is arranged on the side of the negative electrode active material layer away from the negative electrode current collector; wherein the polymer layer comprises a flexible polymer, and the flexible polymer comprises at least one of polyether polyurethane, polyacrylonitrile, polyvinyl alcohol, polyvinyl chloride and polyacrylate.

[0008] According to the negative electrode sheet of the embodiment of the present invention, by arranging a polymer layer on the negative electrode active material layer outside the negative electrode current collector, the polymer layer is used to buffer the sharp protrusions of the negative electrode active material layer and the diaphragm, which can reduce the force of the sharp protrusions on the diaphragm, make the interface between the diaphragm and the negative electrode sheet smoother during the hot pressing process, and reduce the risk of local deformation or damage of the diaphragm. It is also beneficial to protect the negative electrode active material layer, improve the flexibility of the negative electrode sheet, and help reduce the short circuit rate of the battery during the lamination process. At the same time, the polymer layer using the above-mentioned flexible polymer can play the role of an interface film, reduce interface side reactions, and improve cycle performance. At the same time, the internal pores of the polymer layer can provide a good transmission channel for ions. In addition, the polymer layer is light in weight and its effect on the energy density of the negative electrode sheet is negligible.

[0009] According to some embodiments of the present invention, the porosity of the polymer layer is 30% to 60%.

[0010] According to some embodiments of the present invention, the thickness of the polymer layer is 1 μm to 4 μm.

[0011] According to some embodiments of the present invention, the polymer layer further includes a first conductive agent, wherein the first conductive agent includes at least one of conductive carbon black, carbon nanotubes and graphene.

[0012] According to some embodiments of the present invention, the mass proportion of the first conductive agent in the polymer layer is 1% to 5%.

[0013] According to some embodiments of the present invention, the negative electrode active material layer includes an active main material, and the active main material includes first active particles and / or second active particles, wherein the particle size of the first active particles is larger than the particle size of the second active particles, the D50 particle size of the first active particles is 4.2μm~8.1μm, and the D50 particle size of the second active particles is 1.1μm~3.0μm.

[0014] According to some embodiments of the present invention, a weight ratio of the first active particles to the second active particles in the negative electrode active material layer is (7:3) to (9:1).

[0015] According to some embodiments of the present invention, the negative electrode active material layer further includes a second conductive agent, and the mass proportion of the second conductive agent in the negative electrode active material layer is 1% to 3%.

[0016] According to some embodiments of the present invention, the negative electrode active material layer also includes a binder and / or a dispersant, wherein the mass proportion of the binder in the negative electrode active material layer is 1% to 3%; and / or the mass proportion of the dispersant in the negative electrode active material layer is 1% to 3%.

[0017] According to some embodiments of the present invention, the negative electrode current collector includes a copper foil, an aluminum foil, a Cu / pp / Cu, a Cu / PET / Cu, an Al / pp / Al or an Al / PET / Al three-layer composite current collector.

[0018] According to the second aspect of the present invention, the method for preparing a negative electrode sheet comprises: spraying a polymer layer slurry, melt-blowing the polymer layer or laminating a polymer layer film on a side of the negative electrode active material layer away from the negative electrode current collector.

[0019] According to the third aspect of the present invention, the battery comprises: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the negative electrode sheet is the negative electrode sheet according to the first aspect of the present invention, or the negative electrode sheet prepared by the preparation method of the second aspect of the present invention.

[0020] An electrical device according to an embodiment of a fourth aspect of the present invention includes: a battery according to an embodiment of the third aspect of the present invention.

[0021] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 Schematic diagram of a negative electrode sheet according to an embodiment of the present invention.

[0023] Reference numerals: 100: negative electrode; 1: negative electrode current collector; 2: negative electrode active material layer; 21: first active particles; 22: second active particles; 3: polymer layer; 4: second conductive agent; 5: binder. DETAILED DESCRIPTION

[0024] Reference below Figure 1 The negative electrode sheet 100 according to the first embodiment of the present invention is described.

[0025] like Figure 1 As shown, the negative electrode sheet 100 according to the first embodiment of the present invention includes a negative electrode current collector 1 , a negative electrode active material layer 2 and a polymer layer 3 .

[0026] Specifically, the negative electrode active material layer 2 is disposed on the negative electrode current collector 1. The polymer layer 3 is disposed on the side of the negative electrode active material layer 2 away from the negative electrode current collector 1. The polymer layer 3 includes a flexible polymer, and the flexible polymer includes at least one of polyether polyurethane, polyacrylonitrile, polyvinyl alcohol, polyvinyl chloride and polyacrylate.

[0027] For example, in Figure 1 In the example, a negative electrode active material layer 2 and a polymer layer 3 are sequentially arranged on the negative electrode current collector 1 in a direction away from the negative electrode current collector 1. Among them, the negative electrode current collector 1 is used to provide a transmission path for electrons from an external circuit to the negative electrode active material layer 2, and also has good mechanical strength to support the battery structure. The negative electrode active material layer 2 can absorb or release ions during the charging and discharging process of the battery. The polymer layer 3 has good flexibility, and acts as a buffer between the sharp protrusions of the negative electrode active material layer 2 and the diaphragm, which can reduce the force of the sharp protrusions on the diaphragm. At the same time, the polymer layer 3 also helps to obtain a flat surface of the negative electrode sheet 100, so that the interface between the diaphragm and the negative electrode sheet 100 is smoother during the hot pressing process, which can reduce the risk of local deformation or damage of the diaphragm and reduce the short circuit rate of the battery during the lamination process.

[0028] Among them, at least one of polyether polyurethane, polyacrylonitrile, polyvinyl alcohol, polyvinyl chloride and polyacrylate as the flexible polymer has the following advantages: First, the flexible polymer has good flexibility, which is beneficial to protecting the negative electrode active material layer 2, preventing the active material in the negative electrode active material layer 2 from collapsing, and improving the cycle performance; Second, the porosity of the flexible polymer is large, which can easily meet the needs of the polymer layer 3, that is, allow the electrolyte to pass through the polymer layer 3. At the same time, the polymer layer 3 has good chemical stability in the electrolyte and will not have side reactions with the electrolyte. Third, the decomposition temperature of the above-mentioned flexible polymer is high, which can effectively prevent the polymer layer 3 from decomposing after the battery is heated during operation, thereby improving the stability of the polymer layer 3; Fourthly, the above-mentioned flexible polymer has good wettability, which ensures the penetration of the electrolyte into the polymer layer 3 and helps to prevent local overheating and other uneven phenomena of the polymer layer 3; Fifth, the thickness of the flexible polymer layer is thin, and the conductive agent uniformly dispersed therein can improve the electronic conductivity of the surface layer, which will not cause the internal resistance of the negative electrode sheet 100 to increase, and can meet the internal resistance and power performance requirements of the negative electrode sheet 100.

[0029] Thus, the polymer layer 3 using the above-mentioned flexible polymer can play the role of an interface film, reduce interface side reactions, and improve cycle performance. At the same time, the internal pores of the polymer layer 3 can provide a good transmission channel for ions. The polymer layer 3 is light in weight and has a negligible effect on the energy density of the negative electrode sheet 100.

[0030] According to the negative electrode sheet 100 of the embodiment of the present invention, by setting a polymer layer 3 on the negative electrode active material layer 2 outside the negative electrode current collector 1, the polymer layer 3 plays a buffering role between the sharp protrusions of the negative electrode active material layer 2 and the diaphragm, which can reduce the force of the sharp protrusions on the diaphragm, make the interface between the diaphragm and the negative electrode sheet 100 smoother during the hot pressing process, and reduce the risk of local deformation or damage of the diaphragm. It is also beneficial to protect the negative electrode active material layer 2, improve the flexibility of the negative electrode sheet 100, and help reduce the short circuit rate of the battery during the lamination process. At the same time, the polymer layer 3 using the above-mentioned flexible polymer can play the role of an interface film, reduce interface side reactions, and improve cycle performance. At the same time, the internal pores of the polymer layer 3 can provide a good transmission channel for ions. In addition, the polymer layer 3 is light in weight and has a negligible effect on the energy density of the negative electrode sheet 100.

[0031] According to some embodiments of the present invention, the porosity of the polymer layer 3 is 30% to 60%. Porosity refers to the ratio of the volume of pores in the polymer layer 3 to the total volume of the entire polymer layer 3. Therefore, the porosity of the polymer layer 3 is relatively reasonable, which fully allows the electrolyte to pass through the polymer layer 3, and helps to improve the wettability of the polymer layer 3.

[0032] The porosity of polymer layer 3 is measured by liquid absorption method. Specifically, at room temperature, polymer layer 3 is directly coated on the surface of aluminum foil, and after drying, it is prepared into a small round piece sample with a diameter of 19 mm together with the aluminum foil using a punching machine. Then, the thickness of the sample is measured using a Marr thickness gauge. After deducting the thickness of the aluminum foil, the thickness of polymer layer 3 can be obtained, and the volume V of polymer layer 3 is calculated; the weight of the sample is weighed, recorded as W0; soaked in n-butanol for 2 hours, the density of n-butanol is ρ; use filter paper to absorb the excess liquid on the surface of the sample and weigh it, recorded as W1. The porosity of polymer layer 3 is calculated using the following formula: .

[0033] According to some embodiments of the present invention, the thickness of the polymer layer 3 is 1 μm to 4 μm. The polymer layer 3 within the above thickness range is arranged on the surface of the negative electrode active material, which can give full play to the role of the interface film of the polymer layer 3, reduce the interface side reaction, improve the first efficiency of the battery, and reduce the electrolyte consumption and the pulverization and collapse of the active material structure during the cycle, thereby improving the cycle performance. In addition, the polymer layer 3 is thin and light, which is beneficial to improve the energy density of the negative electrode sheet 100 compared to the conventional negative electrode sheet 100 with a thick diaphragm to optimize the short circuit rate. At the same time, it can avoid the increase of the internal resistance of the negative electrode sheet 100 due to the increase of the thickness of the polymer layer 3 on the surface.

[0034] According to other embodiments of the present invention, the polymer layer 3 further includes a first conductive agent, which includes at least one of conductive carbon black, carbon nanotubes and graphene. The function of the first conductive agent is to enhance the conductivity of the polymer layer 3 and prevent the internal resistance of the negative electrode sheet 100 from increasing. At least one of the above conductive agents is used as the first conductive agent, so that the first conductive agent dispersed in the polymer layer 3 can effectively improve the electronic conductivity of the polymer layer 3.

[0035] Furthermore, the mass proportion of the first conductive agent in the polymer layer 3 is 1% to 5%. The amount of the first conductive agent in the polymer layer 3 is relatively reasonable, which is conducive to giving full play to the role of the first conductive agent, effectively improving the conductivity of the polymer layer 3, and avoiding excessive reduction of the flexibility of the polymer layer 3 by the first conductive agent.

[0036] According to some embodiments of the present invention, the negative electrode active material layer 2 includes an active main material, and the active main material includes first active particles 21 and / or second active particles 22. The particle size of the first active particles 21 is larger than that of the second active particles 22, the D50 particle size of the first active particles 21 is 4.2μm to 8.1μm, and the D50 particle size of the second active particles 22 is 1.1μm to 3.0μm. The active main material is the core component of the negative electrode active material layer 2, which directly determines the key performance indicators of the battery, such as the energy density, cycle life and safety. The active main material may include only the first active particles 21 (not shown) or only the second active particles 22 (not shown); or, the active main material may include both the first active particles 21 and the second active particles 22 (such as Figure 1 As shown). There are gaps between the first active particles 21 and the first active particles 21, or between the second active particles 22 and the second active particles 22, or between the first active particles 21 and the second active particles 22, so that the negative electrode active material layer 2 formed is a porous structure, and thus the negative electrode active material layer 2 has good charge and discharge performance and power performance.

[0037] Reference Figure 1 When the active main material includes the first active particles 21 and the second active particles 22, the particle size of the first active particles 21 is larger and the particle size of the second active particles 22 is smaller, so that the second active particles 22 can be filled into the gaps between the first active particles 21, which can reduce the roughness of the surface of the negative electrode active material layer 2, reduce the short circuit rate, and improve the compaction density of the negative electrode active material layer 2.

[0038] Furthermore, the weight ratio of the first active particles 21 and the second active particles 22 in the negative electrode active material layer 2 is (7:3) to (9:1). As a result, the weight ratio of the first active particles 21 and the second active particles 22 is relatively reasonable, so that the second active particles 22 with smaller particle sizes can be fully filled in the gaps between the first active particles 21 with larger particle sizes, which is conducive to reducing the sharp protrusions of the negative electrode active material layer 2 as much as possible, thereby improving the flatness of the negative electrode active material layer 2. In addition, the use of the above-mentioned negative electrode active material layer 2 in combination with the polymer layer 3 is conducive to improving the surface flatness of the negative electrode sheet 100, making the interface between the separator and the negative electrode sheet 100 relatively flat during the hot pressing process, effectively reducing the local deformation of the separator and reducing the risk of separator damage.

[0039] Furthermore, the negative electrode active material layer 2 also includes a second conductive agent 4, and the mass proportion of the second conductive agent 4 in the negative electrode active material layer 2 is 1% to 3%. The second conductive agent 4 can help improve the conductivity of the negative electrode active material layer 2. The above-mentioned second conductive agent 4 has high conductivity, good dispersibility, good compatibility and good improvement on battery performance. Therefore, the use of the second conductive agent 4 with the above-mentioned mass proportion is conducive to compensating for the problem of insufficient conductivity of the active main material, while avoiding the addition of too much second conductive agent 4 to occupy active sites and affect the ion storage capacity of the negative electrode active material layer 2, and can also avoid the addition of too little second conductive agent 4 to form an effective conductive network.

[0040] Furthermore, the negative electrode active material layer 2 also includes a binder 5 and / or a dispersant. The binder 5 can bind the active main material and the second conductive agent 4 together to form a stable negative electrode active material layer 2, and also fix the negative electrode active material layer 2 on the negative electrode current collector 1, thereby ensuring the mechanical integrity of the negative electrode sheet 100 during the charging or discharging process of the battery. Among them, the binder 5 has good mechanical strength and chemical stability to improve the use stability of the binder 5 and avoid degradation during the operation of the battery.

[0041] The presence of the dispersant can reduce the viscosity of the slurry of the negative electrode active material layer 2, making the slurry of the negative electrode active material layer 2 easier to apply and less likely to produce cracks or unevenness when drying to form the negative electrode active material layer 2, thereby improving the mechanical strength of the negative electrode active material layer 2 and improving the electrochemical performance of the negative electrode sheet 100.

[0042] Among them, the mass proportion of the binder 5 in the negative electrode active material layer 2 is 1% to 3%. The addition amount of the binder 5 is relatively reasonable, which is conducive to giving full play to the role of the binder 5, thereby improving the structural stability of the negative electrode active material layer 2, and at the same time, it is conducive to improving the reliability and stability of the negative electrode active material layer 2 on the negative electrode current collector 1.

[0043] The mass proportion of the dispersant in the negative electrode active material layer 2 is 1% to 3%. The amount of the dispersant added is relatively reasonable, which is conducive to giving full play to the role of the dispersant, and improving the uniformity of the slurry of the negative electrode active material layer 2 and the negative electrode material layer, thereby improving the quality of the negative electrode active material layer 2.

[0044] Furthermore, the negative electrode current collector 1 includes a three-layer composite current collector of copper foil (Cu), aluminum foil (Al), Cu / pp (polypropylene) / Cu, Cu / PET (polyethylene terephthalate) / Cu, Al / pp / Al or Al / PET / Al. The above-mentioned negative electrode current collectors 1 have good conductivity, can ensure the effective transmission of current, and have good chemical stability during the charging and discharging process. The above-mentioned negative electrode current collector 1 has good compatibility with other materials in the battery (electrolyte, etc.), can avoid the occurrence of side reactions, and improve the use stability of the negative electrode current collector 1. In addition, the above-mentioned negative electrode current collector 1 has a high mechanical strength, which is conducive to enriching the application of the negative electrode sheet 100 of the above-mentioned negative electrode current collector 1 in various batteries, thereby helping to improve the market competitiveness of the above-mentioned negative electrode sheet 100 and the battery using the above-mentioned negative electrode sheet 100.

[0045] The method for preparing the negative electrode sheet 100 according to the second embodiment of the present invention comprises: spraying a polymer layer slurry, a melt-blown polymer layer 3 or a laminated polymer layer film on the side of the negative electrode active material layer 2 away from the negative electrode current collector 1 .

[0046] Among them, spraying is a method of spraying a liquid or molten polymer layer 3 slurry in a mist state onto the surface of the negative electrode active material layer 2 away from the negative electrode current collector 1 to form the polymer layer 3. Melt blowing is a technology that uses a high-speed hot air flow to blow a molten polymer into filaments to form a fiber mesh polymer layer 3. Lamination is to first prepare a polymer layer film, and then apply pressure, heat or adhesive to achieve the polymer layer 3 on the surface of the negative electrode active material layer 2 away from the negative electrode current collector 1.

[0047] According to the method for preparing the negative electrode sheet 100 of the embodiment of the present invention, the preparation method is relatively simple, and the quality of the prepared polymer layer 3 is relatively uniform, and the thickness of the prepared polymer layer 3 can easily meet the needs of the negative electrode sheet 100, thereby helping to improve the preparation efficiency and quality of the negative electrode sheet 100.

[0048] The battery according to the third aspect of the present invention comprises: a positive electrode sheet, a negative electrode sheet 100, a separator and an electrolyte; wherein the negative electrode sheet 100 is the negative electrode sheet 100 according to the first aspect of the present invention, or the negative electrode sheet 100 prepared by the preparation method of the second aspect of the present invention.

[0049] By using the above-mentioned negative electrode sheet 100, for example, during the hot pressing process of preparing the battery, the negative electrode sheet 100 exerts less force on the diaphragm, and the short-circuit rate of the core voltage test after hot pressing is lower; the negative electrode sheet 100 has better flexibility, which can improve the problem of material falling during the bending process and reduce the possibility of short circuit caused by foreign matter; when using the same type of diaphragm, it is beneficial to increase the insulation gap between the positive electrode sheet and the negative electrode sheet 100, improve the ability of the core to resist voltage breakdown, and reduce the short-circuit rate of the core during the voltage test after hot pressing.

[0050] At the same time, the polymer layer 3 of the negative electrode sheet 100 can play the role of an interface film, reduce interface side reactions, and improve the initial efficiency of the battery; it can also reduce the consumption of electrolyte and the pulverization and collapse of the active material structure during the battery cycle, and improve the cycle performance.

[0051] In addition, the polymer layer 3 can reduce the force exerted by the sharp protrusions on the surface of the negative electrode sheet 100 on the separator, making the interface between the separator and the negative electrode sheet 100 smoother during hot pressing, thereby reducing the risk of local deformation or damage of the separator.

[0052] The battery according to the embodiment of the present invention is helpful to reduce the impact of the negative electrode sheet 100 on the electrolyte and the separator, thereby helping to improve the use stability and reliability of the battery, and further helping to improve the market competitiveness of the battery.

[0053] An electrical device according to an embodiment of a fourth aspect of the present invention includes: a battery according to an embodiment of the third aspect of the present invention.

[0054] The electric device according to the embodiment of the present invention adopts the above-mentioned battery, which is beneficial to improving the energy supply stability and reliability of the electric device, improving the operation stability and smoothness of the electric device, and thus helping to improve the user experience of the electric device.

[0055] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0056] Example 1 This embodiment takes a negative electrode sheet 100 with a surface-sprayed polymer layer 3 and a negative electrode active material layer 2 composed of a combination of first active particles 21 and second active particles 22 as an example.

[0057] Step 1: Prepare the negative electrode active material layer 2 composed of the first active particles 21 and the second active particles 22 The formula of the slurry of the negative electrode active material layer 2 is: by mass ratio, the first active particles 21 (D50 particle size is 6.2μm): the second active particles 22 (D50 particle size is 1.5μm): conductive carbon black: styrene-butadiene rubber: sodium carboxymethyl cellulose (CMC) = 70:30:1:1:2, dispersed in an appropriate amount of deionized water, wherein the solid content of the slurry of the negative electrode active material layer 2 is 59%.

[0058] (1) Use deionized water as solvent, add sodium carboxymethyl cellulose and disperse evenly to form a transparent glue solution; (2) Add the second conductive agent 4 (conductive carbon black) and disperse evenly at high speed; (3) Add the second active particles 22 in batches and stir to mix evenly; (4) Add the first active particles 21 in batches and stir to mix evenly; (5) Add styrene-butadiene rubber (SBR) and mix well to obtain a slurry of the negative electrode active material layer 2; (6) The slurry of the negative electrode active material layer 2 is coated on an aluminum foil (thickness of 13 μm), and after baking and rolling, a negative electrode active material layer 2 is obtained, wherein the surface density of the negative electrode active material layer 2 is 180 g / m 2 .

[0059] Step 2: Prepare a negative electrode sheet 100 having a polymer layer 3 on the surface The formula of the slurry of the polymer layer 3 is: by mass ratio, polyether polyurethane: first conductive agent: water: N-methylpyrrolidone (NMP) = 95:5:1425:475. The solid content of the slurry of the polymer layer 3 is 5%, and the molecular weight of the polyether polyurethane is 10,000-80,000.

[0060] (1) Using a mixture of deionized water and NMP as solvent, add polyether polyurethane and disperse evenly; (2) adding a first conductive agent (conductive carbon black) and dispersing it evenly at high speed to obtain a slurry of the polymer layer 3; (3) coating the slurry of the polymer layer 3 onto the surface of the negative electrode active material layer 2 prepared in step 1, and drying at a temperature of 70° C. to 90° C.; (4) By adjusting the proportion of NMP in the solvent, the drying temperature, the wind speed and the wind frequency, the porosity of the polymer layer 3 is adjusted to 45%, and the thickness of the polymer layer 3 after rolling is controlled to be 2 μm by adjusting the surface density of the polymer layer 3. After die-cutting, the negative electrode sheet 100 with the polymer layer 3 on the surface is obtained.

[0061] Step 3: Prepare the positive electrode The coating slurry formula of the positive electrode sheet is: by mass ratio, sodium iron pyrophosphate (D50 particle size is 5.8μm): conductive agent: binder 5 = 100:2:2, wherein the solid content of the coating slurry of the above positive electrode sheet is 58%.

[0062] (1) Using N-methylpyrrolidone (NMP) as solvent, add binder 5 polyvinylidene fluoride (PVDF) and disperse evenly to form a transparent glue solution; (2) Add a conductive agent (one or more conductive agents such as carbon black, carbon nanotubes, graphene, etc.) and disperse evenly at high speed; (3) adding sodium iron pyrophosphate material in batches, stirring and mixing evenly to obtain a coating slurry for the positive electrode sheet; (4) The coating slurry of the positive electrode sheet is coated on an aluminum foil (thickness of 13 μm), and after baking, rolling and die-cutting, a positive electrode sheet is obtained. The surface density of the positive electrode active material layer of the positive electrode sheet is controlled to be 465 g / m 2 .

[0063] The negative electrode sheet 100 with the polymer layer 3 on the surface prepared in step 1 and step 2 and the positive electrode sheet prepared in step 3 are stacked with the separator to obtain a pole core. The stacking method includes layer stacking or Z stacking.

[0064] Example 2 This embodiment takes a negative electrode sheet 100 with a surface-coated polymer layer 3 and a negative electrode active material layer 2 composed of a first active particle 21 and a second active particle 22 as an example.

[0065] The difference between Example 2 and Example 1 is that in step 2 of Example 2, the formula of the slurry of the polymer layer 3 is: by mass ratio, polyvinyl alcohol (PVA): first conductive agent: water: N-methylpyrrolidone (NMP) = 95:5:1425:475, wherein the solid content of the slurry of the above-mentioned polymer layer 3 is 5%, and the molecular weight of PVA is 118000-124000.

[0066] Example 3 This embodiment takes the negative electrode sheet 100 in which the surface is coated with the polymer layer 3 and the negative electrode active material layer 2 are all of a D50 particle size of 6.2 μm as an example.

[0067] The difference between Example 3 and Example 1 is that in step 1 of Example 3, the slurry formula of the negative electrode active material layer 2 is as follows: by mass ratio, the solid mass ratio of the first active particles 21: the second conductive agent 4: styrene-butadiene rubber: sodium carboxymethyl cellulose is 100:1:1:2.

[0068] Example 4 This embodiment takes a negative electrode sheet 100 with a surface-coated polymer layer 3 and a negative electrode active material layer 2 composed of a first active particle 21 and a second active particle 22 as an example.

[0069] The difference between Example 4 and Example 1 is that in step 2 of Example 4, the thickness of the polymer layer 3 is 1 μm.

[0070] Example 5 This embodiment takes a negative electrode sheet 100 with a surface-coated polymer layer 3 and a negative electrode active material layer 2 composed of a first active particle 21 and a second active particle 22 as an example.

[0071] The difference between Example 5 and Example 1 is that in step 2 of Example 5, the thickness of the polymer layer 3 is 4 μm.

[0072] Example 6 This embodiment takes a negative electrode sheet 100 with a surface-coated polymer layer 3 and a negative electrode active material layer 2 composed of a first active particle 21 and a second active particle 22 as an example.

[0073] The difference between Example 6 and Example 1 is that in step 2 of Example 6, the slurry formula of the polymer layer 3 is: in terms of mass ratio, polyether polyurethane: conductive agent: water: N-methylpyrrolidone (NMP) = 99:1:1425:475.

[0074] Example 7 This embodiment takes a negative electrode sheet 100 with a surface-coated polymer layer 3 and a negative electrode active material layer 2 composed of a first active particle 21 and a second active particle 22 as an example.

[0075] The difference between Example 7 and Example 1 is that in step 2 of Example 7, the slurry formula of the polymer layer 3 is: in terms of mass ratio, polyether polyurethane: conductive agent: water: N-methylpyrrolidone (NMP) = 97:3:1425:475.

[0076] Example 8 This embodiment takes a negative electrode sheet 100 with a surface-coated polymer layer 3 and a negative electrode active material layer 2 composed of a first active particle 21 and a second active particle 22 as an example.

[0077] The difference between Example 8 and Example 1 is that in step 2 of Example 8, the porosity of the polymer layer 3 is 30%.

[0078] Example 9 This embodiment takes a negative electrode sheet 100 with a surface-coated polymer layer 3 and a negative electrode active material layer 2 composed of a first active particle 21 and a second active particle 22 as an example.

[0079] The difference between Example 9 and Example 1 is that in step 2 of Example 9, the porosity of the polymer layer 3 is 60%.

[0080] Example 10 This embodiment takes a negative electrode sheet 100 with a surface-coated polymer layer 3 and a negative electrode active material layer 2 composed of a first active particle 21 and a second active particle 22 as an example.

[0081] The difference between Example 10 and Example 1 is that in step 1 of Example 10, the slurry formula of the negative electrode active material layer 2 is: by mass ratio, first active particles 21 (D50 particle size is 6.2 μm): second active particles 22 (D50 particle size is 1.5 μm): second conductive agent 4: styrene-butadiene rubber: sodium carboxymethyl cellulose = 80:20:1:1:2.

[0082] Embodiment 11 This embodiment takes the negative electrode sheet 100 having a surface-coated polymer layer 3 , a negative electrode active material layer 2 , first active particles 21 , and second active particles 22 as an example.

[0083] The difference between Example 11 and Example 1 is that in step 1 of Example 11, the slurry formula of the negative electrode active material layer 2 is: by mass ratio, first active particles 21 (D50 particle size is 6.2 μm): second active particles 22 (D50 particle size is 1.5 μm): conductive carbon black: styrene-butadiene rubber: sodium carboxymethyl cellulose = 90:10:1:1:2.

[0084] Comparative Example 1 The negative electrode sheet 100 of this comparative example has no polymer layer 3 on its surface, and the negative electrode active material layer 2 is entirely composed of active particles with a D50 particle size of 6.2 μm.

[0085] Step 1: Prepare the negative electrode sheet 100 The slurry formula of the negative electrode active material layer 2 is: by mass ratio, hard carbon active particles: conductive carbon black: styrene-butadiene rubber: sodium carboxymethyl cellulose = 100:1:1:2, dispersed in an appropriate amount of deionized water, and its solid content is 59%.

[0086] 1) Use deionized water as solvent, add sodium carboxymethyl cellulose (CMC) and disperse evenly to form a transparent glue solution; 2) Add the second conductive agent 4 (conductive carbon black) and disperse evenly at high speed; 3) Add hard carbon active particles in batches and stir to mix evenly; 4) Add styrene-butadiene rubber (SBR) and mix well to obtain a slurry of the negative electrode active material layer 2; 5) The slurry of the negative electrode active material layer 2 is coated on a 13 μm aluminum foil, and after baking, rolling and die-cutting, a negative electrode sheet 100 is obtained. The surface density of the negative electrode active material layer 2 is 180 g / m 2 .

[0087] Step 2: Prepare the positive electrode The method for preparing the positive electrode sheet is the same as step three in Example 1.

[0088] The negative electrode sheet 100 prepared in step 1 and the positive electrode sheet prepared in step 2 are stacked with a separator to obtain a pole core, and the stacking method includes layer stacking or Z stacking.

[0089] Comparative Example 2 The surface of the negative electrode sheet 100 of the comparative example has no polymer layer 3 , and the negative electrode active material layer 2 is a negative electrode sheet 100 in which the first active particles 21 and the second active particles 22 are matched.

[0090] The difference between Comparative Example 2 and Comparative Example 1 is that in step 1, the slurry formula of the negative electrode active material layer 2 is: by mass ratio, first active particles 21 (D50 particle size is 6.2 μm): second active particles 22 (D50 particle size is 1.5 μm): conductive carbon black: styrene-butadiene rubber: sodium carboxymethyl cellulose = 70:30:1:1:2.

[0091] Table 1 Structural data of Examples 1-11 and Comparative Examples 1-2

[0092] Performance testing and result analysis (1) Test of Hi-pot yield of the core after hot pressing at different pressures The battery in the embodiment and comparative example is equipped with 14PP+3F (polypropylene with a thickness of 14μm + PVDF with a thickness of 3μm) diaphragm, wherein only one side of the thickness direction of the polypropylene in the diaphragm is provided with PVDF. When stacking, the PVDF side of the diaphragm faces the positive electrode sheet, and hot pressing is performed under 75kPa, 150kPa, and 200kPa hot pressing pressure conditions for 360 seconds, and then a Hi-pot withstand voltage test is performed under 200V, 250ms conditions. 2000 pole cores are tested in each case to evaluate the short circuit rate of the hot pressing test. The test results are shown in Table 2.

[0093] Table 2 Hi-pot yield data of the core after hot pressing at different pressures for Examples 1-11 and Comparative Examples 1-2

[0094] As can be seen from Table 2, compared with Comparative Example 1, the Hi-pot yields of Examples 1-11 and Comparative Example 2 under different hot pressing pressure conditions are improved. Taking the 75 kPa hot pressing pressure condition as an example, compared with Comparative Example 1, the yield of Comparative Example 2 is improved by 1.2%, indicating that the combination of the first active particles 21 and the second active particles 22 has a certain effect on reducing the short circuit rate of the Hi-pot withstand voltage test after the core hot pressing. Compared with comparative example 1, the yield of Example 3 is increased by 2.5%, indicating that the 2μm flexible polyurethane layer on the surface of the negative electrode sheet 100 can effectively reduce the short circuit rate of the Hi-pot withstand voltage test after the core is hot pressed; compared with comparative example 1, the yield of Example 1 is increased by 3.4%, indicating that the 2μm flexible polyurethane layer on the surface of the negative electrode sheet 100 and the negative electrode active material layer 2 with the first active particles 21 and the second active particles 22 can be used in combination to significantly reduce the Hi-pot short circuit rate after the core is hot pressed; compared with comparative example 1, the yield of Example 2 is increased by 3.1%, indicating that the surface flexible PVA layer and the flexible polyurethane layer have similar effects on improving the yield of the Hi-pot withstand voltage test after the battery is hot pressed. The combination of the first active particles 21 and the second active particles 22 can reduce the surface roughness of the negative electrode active material layer 2 and reduce the short circuit rate. The polymer layer 3 wraps the sharp positions on the surface, making the surface of the negative electrode sheet 100 flexible, playing a buffering role between the sharp protrusions of the negative electrode active material layer 2 and the diaphragm, and reducing the force of the sharp protrusions on the diaphragm; at the same time, it can also increase the insulation gap, improve the material dropout during the bending process of the negative electrode sheet 100, and reduce the short circuit rate of the electrode core during the voltage withstand test after hot pressing.

[0095] Taking 75kPa hot pressing pressure condition as an example, compared with Example 1, the yield of Example 4 is reduced by 2.0%, and the yield of Example 5 is increased by 0.7%, indicating that when the thickness of the polymer layer 3 is thickened in the range of 1μm to 4μm, the short-circuit rate of the Hi-pot withstand voltage test after the pole core is hot pressed can be reduced, and it can be considered that the increase in the insulation gap brings about the improvement of the short-circuit rate; compared with Example 1, there is no obvious difference in the yield of Example 6 and Example 7, indicating that when the conductive agent content in the polymer layer 3 changes in the range of 1% to 5%, it has no effect on the short-circuit rate of the Hi-pot withstand voltage test after the pole core is hot pressed; compared with Example 1, the yield of Example 8 is increased by 0.4%, and the yield of Example 9 is reduced by 1.3%, indicating that the porosity of the polymer layer 3 When it decreases within the range of 30% to 60%, the short-circuit rate of the Hi-pot withstand voltage test after hot pressing of the pole core can be reduced. The reduction in porosity means that the coverage of the sharp positions on the surface of the negative electrode active material layer 2 by the polymer layer 3 increases, so that the area where short circuit may occur is reduced and the short-circuit rate is reduced. Compared with Example 1, the yield of Example 10 is reduced by 0.5%, and the yield of Example 11 is reduced by 0.7%, indicating that when the ratio of the first active particles 21 to the second active particles 22 in the negative electrode active material layer 2 changes within the range of 7:3 to 9:1, it has a slight effect on the short-circuit rate of the Hi-pot withstand voltage test after hot pressing of the pole core. When the proportion of the second active particles 22 is increased, the surface roughness of the negative electrode active material layer 2 after rolling can be reduced, and the short-circuit rate is reduced.

[0096] (2) Hi-pot yield test after hot pressing of batteries with different diaphragms The batteries in the embodiments and comparative examples respectively use 14PP+3F (polypropylene with a thickness of 14 μm + PVDF with a thickness of 3 μm), wherein only one side of the polypropylene in the diaphragm in the thickness direction is provided with PVDF, 14PE+3F (PE is polyethylene), 16PP+3F, 14PE+2C+3F (polyethylene with a thickness of 14 μm + ceramic with a single-sided thickness of 2 μm + PVDF with a single-sided thickness of 3 μm) diaphragms, wherein only one side of the polyethylene in the diaphragm in the thickness direction is provided with ceramic and PVDF for stacking, hot pressing for 360 seconds under 75 kPa hot pressing pressure conditions, and then performing a Hi-pot withstand voltage test under 200 V, 250 ms conditions. 2000 batteries are tested in each case to evaluate the battery short circuit rate. The test results are shown in Table 3.

[0097] Table 3 Hi-pot yield data of battery with different diaphragms after hot pressing of Examples 1-11 and Comparative Examples 1-2

[0098] It can be seen from Table 3 that when using the same material and thickness of the diaphragm, compared with Comparative Example 1, the Hi-pot yield of Examples 1-11 and Comparative Example 2 is improved, further confirming that the combination of the polymer layer 3 and the first active particles 21 and the second active particles 22 can reduce the short circuit rate. Taking the combination of 16PP+3F as an example, compared with comparative example 1, the yield of comparative example 2 is increased by 0.7%, indicating that the combination of the first active particles 21 and the second active particles 22 has a certain effect on reducing the Hi-pot short-circuit rate after hot pressing of the pole core; compared with comparative example 1, the yield of embodiment 3 is increased by 2.1%, indicating that the 2μm flexible polyurethane layer on the surface of the negative electrode sheet 100 can effectively reduce the Hi-pot short-circuit rate after hot pressing of the pole core; compared with comparative example 1, the yield of embodiment 1 is increased by 2.7%, indicating that the 2μm flexible polyurethane layer on the surface of the negative electrode sheet 100 and the negative electrode active material layer 2 combined with the first active particles 21 and the second active particles 22 can significantly reduce the Hi-pot short-circuit rate after hot pressing of the pole core; compared with comparative example 1, the yield of embodiment 2 is increased by 2.5%, indicating that the surface flexible PVA layer and the flexible polyurethane layer have similar effects on improving the Hi-pot short-circuit rate after hot pressing of the pole core.

[0099] Compared with the Hi-pot yield of the battery after hot pressing when the 14PP+3F separator is used in Comparative Example 1, the yield is increased by 2% when the 14PE+2C+3F separator is used in Comparative Example 1, indicating that the short circuit rate can be effectively reduced by coating the 2μm ceramic coating on the separator. Compared with the 14PP+3F separator is used in Comparative Example 1, the yield is increased by 3.4% when the 14PP+3F separator is used in Example 1, the yield is increased by 3.1% when the 14PP+3F separator is used in Example 2, and the yield is increased by 2.5% when the 14PP+3F separator is used in Example 3, indicating that compared with coating the 2μm ceramic coating on the separator, coating the 2μm polymer layer 3 on the surface of the negative electrode active material layer 2 can more significantly improve the short circuit rate of the electrode core after hot pressing. Compared with coating a ceramic layer on the diaphragm, coating a polymer layer 3 on the surface of the pole piece can obtain a pole piece surface with lower roughness. The diaphragm and the pole piece interface play a buffering role during the hot pressing process, which can reduce the local deformation of the diaphragm and reduce the risk of diaphragm damage. In addition, the polymer layer 3 can increase the flexibility of the pole piece, reduce material falling, and reduce the risk of short circuit caused by material falling.

[0100] Taking the 16PP+3F diaphragm condition as an example, the influence of the thickness of the polymer layer 3, the content of the conductive agent, the porosity, and the ratio of the first active particle 21 and the second active particle 22 of the negative electrode active material layer 2 on the short circuit rate of the Hi-pot withstand voltage test after hot pressing of the core is analyzed again. Compared with Example 1, the yield of Example 4 is reduced by 1.8%, and the yield of Example 5 is increased by 0.7%, indicating that when the thickness of the polymer layer 3 is thickened in the range of 1 to 4 μm, the short circuit rate of the Hi-pot withstand voltage test after hot pressing of the core can be reduced. This is due to the improvement of the short circuit rate caused by the increase in the insulation gap; compared with Example 1, there is no obvious difference in the yield of Example 6 and Example 7, indicating that when the content of the conductive agent in the polymer layer 3 changes in the range of 1 to 5%, it has no effect on the short circuit rate of the Hi-pot withstand voltage test after hot pressing of the core; compared with Example 1, the yield of Example 8 is increased by 0.4%, and the yield of Example 9 is reduced by 1.1%, indicating that the porosity of the polymer layer 3 is in the range of 30% to 60%. When the porosity decreases, the short-circuit rate of the Hi-pot withstand voltage test after the core is hot-pressed can be reduced. This is because the reduction in porosity increases the coverage of the sharp positions on the surface of the negative electrode active material layer 2 by the polymer layer 3, reduces the area where short circuits occur, and reduces the short-circuit rate. Compared with Example 1, the yield of Example 10 is reduced by 0.4%, and the yield of Example 11 is reduced by 0.7%, indicating that when the ratio of the first active particles 21 and the second active particles 22 in the negative electrode active material layer 2 changes in the range of (7:3) to (9:1), it has a slight effect on the short-circuit rate of the Hi-pot withstand voltage test after the core is hot-pressed. When the proportion of the second active particles 22 is increased, the surface roughness of the negative electrode active material layer 2 after rolling can be reduced, and the short-circuit rate is reduced.

[0101] (3) Battery level test The differences in gravimetric energy density (GED) and volumetric energy density (VED) between the comparative example and the example at the electrochemical unit level (ECU, consisting of a positive electrode sheet plus a separator plus a negative electrode sheet 100 plus a separator) were calculated.

[0102] Specifically, the GED calculation method is GED = sodium iron pyrophosphate material C / 3 reversible gram capacity * sodium iron pyrophosphate solid weight ratio in the positive electrode active material layer * positive electrode active material layer density * positive electrode active material layer area / ECU weight.

[0103] The VED calculation method is GED = sodium ferric pyrophosphate material C / 3 reversible gram capacity * sodium ferric pyrophosphate solid weight ratio in the positive electrode active material layer * positive electrode active material layer density * positive electrode active material layer area / ECU volume. C / 3 means that the current is 1 / 3 of the capacity value.

[0104] The test results are shown in Table 4.

[0105] Table 4 Battery level parameters of Examples 1-11 and Comparative Examples 1-2

[0106] The embodiments and comparative examples uniformly use 14PP+3F separators for lamination, and hot press for 360 seconds under 75kPa hot press pressure conditions, and compare the parameter differences of the battery layers after hot pressing. As can be seen from Table 4, compared with comparative example 1, the compaction density of the negative electrode active material layer 2 of comparative example 2, embodiment 1, embodiment 2, and embodiments 4 to 9 is increased by 8.9%, the compaction density of the negative electrode active material layer 2 of embodiment 10 is increased by 6.7%, and the compaction density of the negative electrode active material layer 2 of embodiment 11 is increased by 3.3%, indicating that the combination of the first active particles 21 and the second active particles 22 can increase the compaction density of the negative electrode active material layer 2.

[0107] Compared with Comparative Example 1, the GED of Example 5 at the electrochemical unit level ECU is reduced by 0.4%, which can be considered to be caused by the thick polymer layer 3 (4μm); the GED reduction degree of the other examples is within 0.2%, and it can be considered that the surface coating of 2μm flexible polyurethane layer or PVA layer has no obvious effect on GED; compared with Comparative Example 1, the volume energy density (VED) of Example 1 and Example 2 is increased by 3.1%, indicating that the combined use of the surface polymer layer 3 and the negative electrode active material layer 2 with the first active particle 21 and the second active particle 22 can greatly improve VED. By comparing Example 1, Example 10 and Example 11, it can be seen that when the ratio of the first active particle 21 and the second active particle 22 in the negative electrode active material layer 2 changes from 9:1 to 8:2 and then to 7:3, the VED is significantly improved, which is due to the increase in the compactness of the particle packing.

[0108] (4) First-cycle Coulomb efficiency test The capacity of the first cycle of charging and discharging after the battery cell is filled with liquid is recorded. The first cycle coulombic efficiency of the battery cell can be obtained by dividing the discharged capacity by the charged capacity. The test results are shown in Table 5.

[0109] Table 5 Initial effect data of Examples 1-11 and Comparative Examples 1-2

[0110] The embodiments and comparative examples uniformly use 14PP+3F diaphragms for lamination, and are hot pressed for 360 seconds under 75kPa hot pressing pressure conditions. The batteries are welded, shelled, baked, injected, formed, and divided to obtain the sodium ion batteries of the corresponding cases. The coulomb efficiency of the first cycle of the battery is compared (the first cycle discharge capacity / the first cycle total charging capacity). As can be seen from Table 5, compared with Comparative Example 1, the first efficiency of Example 1 is improved by 1.2%, the first efficiency of Example 2 is improved by 1.3%, and the first efficiency of Example 3 is improved by 1.1%, indicating that polymer layer 3 can improve the first efficiency of the battery. Polymer layer 3 can play the role of an interface membrane, which can reduce interface side reactions and improve the first efficiency of the battery.

[0111] By comparing Example 1, Example 4 and Example 5, it can be seen that when the thickness of the polymer layer 3 is 2 μm, the first effect is slightly higher than the first effect when the thickness is 1 μm and 4 μm. When the thickness of the polymer layer 3 is too thin, the interface side reaction cannot be effectively reduced. When it is too thick, the polarization will increase, which is not conducive to the improvement of the first effect. By comparing Example 1, Example 6 and Example 7, it can be seen that when the content of the conductive agent in the polymer layer 3 is reduced, the first effect is reduced. This is because the impedance is large and the energy efficiency is low when the conductive agent content is low. By comparing Example 1, Example 8 and Example 9, it can be seen that when the porosity changes in the range of 30% to 60%, the effect on the first effect is small. When the porosity is too large, the interface side reaction cannot be effectively blocked, which easily leads to a reduction in the first effect. By comparing Example 1, Example 10 and Example 11, it can be seen that the ratio of the first active particles 21 and the second active particles 22 in the negative electrode active material layer 2 has no obvious effect on the first effect.

[0112] (5) DC internal resistance (DCIR) test After capacity division, the batteries of Examples 1-11 and Comparative Examples 1-2 were discharged at 25% SOC with a current rate of 1.5C for 10 seconds to compare the DC internal resistance (DCIR) of the batteries in each case.

[0113] The test results are shown in Table 6.

[0114] Table 6 DCIR data of Examples 1-11 and Comparative Examples 1-2

[0115] According to Table 6, compared with Comparative Example 1, the DCIR of Example 5 increased by 2%, which is believed to be due to the thick thickness of the polymer layer 3 (4 μm), which leads to an increase in the interface reaction resistance; the DCIR of Example 6 increased by 1.8%, and the DCIR of Example 7 increased by 1.6%, which is caused by the low content of the first conductive agent in the polymer layer 3; the DCIR growth rates of the other implementations are all within 1.4%, and it can be considered that the surface polymer layer 3 and the combination of the first active particles 21 and the second active particles 22 have no significant effect on the DCIR. The thickness of the surface polymer layer 3 is thin (the preferred solution is 2 μm), and its internal pores can provide a good transmission channel for ions. The first conductive agent uniformly dispersed therein can improve the electronic conductivity of the surface layer, so the surface polymer layer 3 will not cause the internal resistance to increase. After the first active particles 21 and the second active particles 22 are matched, the negative electrode active material layer 2 is compacted and improved, and the thickness of the negative electrode active material layer 2 is thinned, which has no significant effect on the internal resistance.

[0116] (6) Discharge rate test The sodium ion batteries corresponding to Examples 1-11 and Comparative Examples 1-2 were charged to 3.6 V using a current at a C / 3 rate, and then discharged to 1.5 V using currents at C / 3, 1C, and 3C rates, respectively, to compare the discharge rate performance of the batteries in each case.

[0117] The test results are shown in Table 7.

[0118] Table 7 Discharge rate performance data of Examples 1-11 and Comparative Examples 1-2

[0119] According to Table 7, compared with Comparative Example 1, the capacity ratio of all embodiments discharged at 3C rate conditions varies within 0.5%, indicating that the combination of the surface polymer layer 3 and the first active particles 21 and the second active particles 22 has no significant effect on the rate performance.

[0120] (7) Cyclic performance test Sodium ion batteries corresponding to Examples 1-11 and Comparative Examples 1-2. At 25°C, charge to 3.6V using a current of C / 3, leave for 30 minutes, then discharge to 1.5V using a current of 1C, leave for 30 minutes; cycle under this condition. After every 100 cycles, use the discharge capacity C0 of the last cycle as the capacity of the battery cell at this time to correct the charge and discharge rate in the subsequent cycles. Use this method to test the cycle performance of the batteries in each case.

[0121] The test results are shown in Table 8.

[0122] Table 8 Cyclic performance data of Examples 1-11 and Comparative Examples 1-2

[0123] From the 500-cycle capacity retention rate data in Table 8, it can be seen that compared with Comparative Example 1, the capacity retention rate of Example 1 is increased by 1.4%, the capacity retention rate of Example 2 is increased by 1.2%, and the capacity retention rate of Example 3 is increased by 1.2%. This shows that the polymer layer 3 on the surface of the negative electrode active material layer 2 can improve the battery cycle performance. The polymer layer 3 is an elastic interface film that can reduce the repeated rupture and reconstruction of the SEI film, reduce the consumption of electrolyte during the cycle and the pulverization and collapse of the active material on the electrode surface, and improve the cycle performance.

[0124] Taking the capacity retention rate data of 500 cycles as an example, compared with comparative example 1, the capacity retention rate of Example 1 is increased by 1.4%, Example 4 is increased by 0.2%, and Example 5 is increased by 0.9%, indicating that when the thickness of the flexible polymer is 2 μm, the cycle performance is better than that of 1 μm and 4 μm. It can be considered that when the thickness of the polymer layer 3 is too thin, it cannot effectively block the interface side reactions, and when it is too thick, the impedance will increase, resulting in cycle attenuation.

[0125] Compared with Comparative Example 1, the capacity retention rate of Example 1 is increased by 1.4%, Example 6 is increased by 0.4%, and Example 7 is increased by 0.7%, indicating that the cycle performance when the conductive agent content in the polymer layer 3 is 5% is better than the cycle performance when the content is 1% and 3%. This is because the impedance decreases when the conductive agent content increases, which is conducive to the interfacial reaction.

[0126] Compared with Comparative Example 1, the capacity retention rate of Example 1 is increased by 1.4%, Example 8 is increased by 0.9%, and Example 9 is increased by 1.0%, indicating that the cycle performance is better when the porosity is 45% than that of 30% and 60%. It is believed that when the porosity is too high, the interface side reactions cannot be effectively blocked, and when the porosity is too low, the ion transmission is slow and the impedance is too large, which will have an adverse effect on the cycle process.

[0127] Compared with comparative example 1, the capacity retention rate of Example 1 is increased by 1.4%, Example 10 is increased by 1.1%, and Example 11 is increased by 1.0%, indicating that the ratio of the first active particles 21 and the second active particles 22 of the negative electrode active material layer 2 has no significant effect on the cycle performance.

[0128] Compared with Comparative Example 1, the 100-cycle, 200-cycle, and 500-cycle capacity retention rates of Example 1 were increased by 0.4%, 0.8%, and 1.4%, respectively. It can be seen that as the number of cycles increases, the effect of coating the surface with a flexible polymer layer on the cycle capacity retention rate will become more and more significant. It is believed that coating the surface with a flexible polymer layer can effectively block the interface side reactions and significantly improve the cycle performance.

[0129] Other structures and operations of the battery and electrical equipment according to the embodiments of the present invention are known to those skilled in the art and will not be described in detail here.

[0130] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0131] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A negative electrode sheet, characterized in that: include: Anode current collector; A negative electrode active material layer, wherein the negative electrode active material layer is disposed on the negative electrode current collector; A polymer layer, the polymer layer being disposed on a side of the negative electrode active material layer away from the negative electrode current collector; Wherein, the polymer layer comprises a flexible polymer, and the flexible polymer comprises at least one of polyether polyurethane, polyacrylonitrile, polyvinyl alcohol, polyvinyl chloride and polyacrylate.

2. The negative electrode sheet according to claim 1, characterized in that: The porosity of the polymer layer is 30% to 60%.

3. The negative electrode sheet according to claim 1, characterized in that: The thickness of the polymer layer is 1 μm to 4 μm.

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The polymer layer further includes a first conductive agent including at least one of conductive carbon black, carbon nanotubes, and graphene.

5. The negative electrode sheet according to claim 4, characterized in that: The mass proportion of the first conductive agent in the polymer layer is 1% to 5%.

6. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material layer includes an active main material, and the active main material includes first active particles and / or second active particles. The particle size of the first active particles is larger than that of the second active particles. The D50 particle size of the first active particles is 4.2 μm to 8.1 μm, and the D50 particle size of the second active particles is 1.1 μm to 3.0 μm.

7. The negative electrode sheet according to claim 6, characterized in that: The weight ratio of the first active particles to the second active particles in the negative electrode active material layer is (7:3) to (9:1).

8. The negative electrode sheet according to claim 7, characterized in that: The negative electrode active material layer further includes a second conductive agent, and the mass proportion of the second conductive agent in the negative electrode active material layer is 1% to 3%.

9. The negative electrode sheet according to claim 8, characterized in that: The negative electrode active material layer also includes a binder and / or a dispersant. Wherein, the binder accounts for 1% to 3% by mass in the negative electrode active material layer; and / or, The mass proportion of the dispersant in the negative electrode active material layer is 1% to 3%.

10. The negative electrode sheet according to claim 1, characterized in that: The negative electrode current collector includes copper foil, aluminum foil, Cu / pp / Cu, Cu / PET / Cu, Al / pp / Al or Al / PET / Al three-layer composite current collector.

11. A method for preparing a negative electrode sheet according to any one of claims 1 to 10, characterized in that: include: The polymer layer slurry is sprayed on the side of the negative electrode active material layer away from the negative electrode current collector, the polymer layer is melt-blown, or a polymer layer film is laminated.

12. A battery, characterized in that: include: A positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; wherein the negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 10, or the negative electrode sheet prepared by the preparation method according to claim 11.

13. An electrical equipment, characterized in that: include: The battery according to claim 12.

Citation Information

Cited By

  • Battery cell structure of solid-state battery, solid-state battery, battery manufacturing equipment and battery manufacturing process

    CN120767286A